Operative Treatment of Lateral Humeral Condyle Fractures in Children - Wirmer, Johannes; Kruppa, Christian; Fitze, Guido (European Journal of Pediatric Surgery, 2012)
The operative treatment of lateral humeral condyle fractures in children remains controversial. The result of incorrectly treated fractures may lead to complications such as pseudoarthrosis and severe deformity, with considerable functional and cosmetic restrictions. The aim of this study was to determine whether operative treatment of lateral humeral condyle fractures in children using Screw-wires (Orthofix GmbH, Ottobrunn, Germany) has any advantage over treatment with Kirschner wires (“K-wires”) (aap-Implantate AG, Berlin, Germany). These results were then compared with operative treatment using lag-screw osteosynthesis. We treated surgically 76 cases of fracture of the lateral humeral condyle in children at the Department of Pediatric Surgery in Dresden between 1989 to 2002 and 2004 to 2008, from which 42 were available for follow-up examination. Within this group, there were seven children that were followed-up twice (in 1996 to 2002). Of these, 21 patients were treated with Screw-wires, and another 21 had K-wires inserted. The results were evaluated according to the Dhillon criteria. Only seven patients (17%) had a fair result in the overall grading according to the Dhillon criteria, four after K-wire and three after Screw-wire osteosyntheses. The remaining patients scored good to excellent results. There were no pseudoarthroses. Six patients (14%) had a varisation in the carrying angle between 10 and 16 degrees (three each procedure), and 15 patients (36%) had no difference in the carrying angle at all. Of these 15 patients, 10 were treated with Screw-wire osteosynthesis. Only one patient (2.4%) had a deficit of more than 10 degrees in elbow joint flexion, while only two (4.8%, one each procedure) had a deficit of more than 10 degrees in elbow joint extension, compared with the uninjured arm. Our results demonstrate that the employment of Screw-wire osteosynthesis is superior to the use of K-wires concerning the carrying angle while scoring alike on the other criteria. Compared with the use of lag screws, both treatments (K-wire and Screw-wire osteosyntheses) bear less risk of nonvascular necrosis or small metaphyseal fragment rupture, by comparable results in the overall outcome. Regarding the long-term development of healed fractures, changes in the carrying angle and the range of motion are of a small degree. Considering the results of this study, we recommend the use of Screw-wire osteosynthesis in the operative treatment of lateral humeral condyle fractures in children.
Keywords: joint fracture children; elbow fracture children; humeral lateral condyle; Screw-wire